2017
DOI: 10.1016/s2095-3119(17)61698-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of seven different companion plants on cucumber productivity, soil chemical characteristics and Pseudomonas community

Abstract: Companion cropping can influence cucumber productivity by altering soil chemical characteristics and microbial communities. However, how these alterations affect the growth of cucumber is still unknown. In this study, seven different plant species were selected as companion plants for testing their effects on cucumber productivity. The effects of different companion plants on changes in soil chemical properties such as electrical conductivity (EC) and contents of essential nutrients as well as the structure an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 39 publications
3
10
0
Order By: Relevance
“…In line with this concept, leafy crops based on the SC and NCCC planting systems corroborate the direct effects of the quantity and quality of crop residue that could be supposed as a premise of organic matter input, soil biological function in continuous replanted soil. The results were in line with previous short-term findings that significant changes in soil properties could be expected in various agronomic conditions such as cropping systems, soil health, and organic input [1,2,3].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In line with this concept, leafy crops based on the SC and NCCC planting systems corroborate the direct effects of the quantity and quality of crop residue that could be supposed as a premise of organic matter input, soil biological function in continuous replanted soil. The results were in line with previous short-term findings that significant changes in soil properties could be expected in various agronomic conditions such as cropping systems, soil health, and organic input [1,2,3].…”
Section: Discussionsupporting
confidence: 91%
“…The results indicate that higher yield response was likely caused by greater nutrient deposition and soil biological activation, and these cropping models were beneficial for increased cucumber yield and relief of continuous cropping–based soil sickness. A similar yield-promoting effect was also observed with tomato–celery–cucumber [40], soybean–pigeon pea rotation [34], wheat–cucumber companion cropping [3], and garlic–cucumber [41] systems. The lowest cucumber yield was found with leaf lettuce–cucumber (LLC) during the latter growth period (AW season), and this effect was likely due to the competitive interaction among neighboring plants for resources and nutrients [42].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The fall trial began on 29 July and ended on 6 October, and the specific operation was consistent with that in spring. A more detailed description of the experiment can be referred to (Chang et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…The diversity and composition of the diazotrophic communities were determined by Illumine MiSeq sequencing, and the abundance of diazotrophs was determined by quantitative PCR analysis of the nifH gene. Our previous studies showed that both cucumber growth and yield were adversely affected by continuous monocultures, while intercropping was able to both improve cucumber yield and increase the diversity of the bacterial and fungal communities ( Chang et al, 2017 ; Li and Wu, 2018 ). Thus, we hypothesize that: (1) intercropping might affect the diversity and composition of the diazotrophic community; and (2) the change in the diazotrophic community are related to soil physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%